I have the function:
natListLast : List ℕ → ℕ
natListLast [] = 0
natListLast nats@(x ∷ xs) = v.last (v.fromList nats)
When I do
_ : natListLast (2 l.∷ l.[] l.++ 1 l.∷ l.[]) ≡ 1
_ = refl
I don't get any error.
But when I try to generalize this to an arbitrary List nat
like so:
natListConcatLast : (nats : List ℕ) → natListLast (nats l.++ 1 l.∷ l.[]) ≡ 1
natListConcatLast [] = refl
natListConcatLast nats@(x ∷ xs) = ?
I'm not sure what to replace ?
with.
I tried starting with begin
:
natListConcatLast : (nats : List ℕ) → natListLast (nats l.++ 1 l.∷ l.[]) ≡ 1
natListConcatLast [] = refl
natListConcatLast nats@(x ∷ xs) =
begin
natListLast (nats l.++ 1 l.∷ l.[])
≡⟨⟩
v.last (v.fromList ((x l.∷ xs) l.++ 1 l.∷ l.[]))
≡⟨⟩
?
≡⟨⟩
1
∎
but I get this error:
1 !=
(last (fromList ((x List.∷ xs) l.++ 1 List.∷ List.[]))
| initLast (fromList ((x List.∷ xs) l.++ 1 List.∷ List.[])))
of type ℕ
when checking that the expression 1 ∎ has type
last (fromList ((x List.∷ xs) l.++ 1 List.∷ List.[])) ≡ 1
I'm not sure how to interpret this error. I'm not sure how to deal with | initLast
.
Thanks!
I suggest the following solution:
open import Data.List
open import Data.Nat
open import Relation.Binary.PropositionalEquality using (_≡_ ; refl)
natListLast : List ℕ → ℕ
natListLast [] = 0
natListLast (x ∷ []) = x
natListLast (_ ∷ y ∷ l) = natListLast (y ∷ l)
natListConcatLast : ∀ l → natListLast (l ++ [ 1 ]) ≡ 1
natListConcatLast [] = refl
natListConcatLast (_ ∷ []) = refl
natListConcatLast (_ ∷ _ ∷ l) = natListConcatLast (_ ∷ l)